A Comparison of Malory’s "Tale of King Arthur" with the spanish "Baladro" - Garrigós González, Cristina (Estudios Humanísticos. Filología, 2001)
A Comparison of Malory’s "Tale of King Arthur" with the spanish "Baladro"